A Comprehensive Review on Functional Properties of Fermented Rice Bran - Sivamaruthi, Bhagavathi Sundaram; Kesika, Periyanaina; Chaiyasut, Chaiyavat (Pharmacognosy Reviews)
A predominant by‑product of rice processing is rice bran (RB). The phytochemical composition of the RB varied among the cultivars. RB is rich in oil, phenolic compounds, polysaccharides, proteins, and micronutrients along with more than 100 known antioxidants and bioactive phytonutrients. The crude and purified RB extracts were used in pharmacological, cosmeceuticals, and food industries. Fermentation process improved the phytochemical constituents and enhanced the bioactivity of RB. The fermented RB (FRB) has been reported for the enhanced antioxidant, anti‑cancer, and anti‑inflammatory bowel diseases, anti‑diabetes activities, etc., FRB is used as potent animal feed, especially in poultry industries. RB bioactive principles were studied for their potential application in anti‑aging treatments, and cosmetics. The current manuscript summarizes the changes in the phytochemical content of RB during the fermentation process and functional property of FRB.
Keywords: Antioxidants; fermented rice bran; phytochemicals; rice bran